Short report: Vaccinia virus in humans and cattle in Southwest region of São Paulo State, Brazil - Megid, Jane [UNESP]; Appolinário, Camila Michele [UNESP]; Langoni, Hélio [UNESP]; Pituco, Edviges Maristela; Okuda, Liria Hiromi (American Society of Tropical Medicine and Hygiene, 2008)
A new outbreak of Vaccinia virus was observed in Southwest region of São Paulo State, Brazil. The disease was observed in four small dairy farms with manual milking. Lesions were detected in cattle and in humans previously vaccinated and not vaccinated against smallpox. Although several reports of Vaccinia virus outbreaks have been occurring in Brazil, it was not yet reported in this region. This outbreak reinforces the viral circulation in our country. The disease in persons previously vaccinated and not vaccinated against smallpox reinforces the absence of immunity, the risk to the human health, and the need for more epidemiologic and immunologic studies. Copyright © 2008 by The American Society of Tropical Medicine and Hygiene.